Leadership Strategies for Implementing Inclusive Digital Platforms for Deep Learning in Developing Country Schools - Iloakasia, Adaobi Jennifer (LPPI Yayasan Almahmudi bin Dahlan, 2026)
The rapid adoption of digital technologies in teaching and learning has increased the need for inclusive leadership that ensures equal access to digital learning opportunities for all students. However, poor infrastructure, inadequate funding, and gender disparities in leadership practices continue to hinder the effective implementation of inclusive digital platforms in Nigeria. This study examined leadership strategies for implementing inclusive digital platforms for deep learning in secondary schools in Anambra State, Nigeria, with particular attention to gender differences among school leaders. A descriptive and comparative research design was adopted. A purposive sample of 70 school leaders, comprising 26 males and 44 females, participated in the study. Data were collected using a validated questionnaire measuring inclusion practices, engagement strategies, and implementation challenges. The instrument yielded a reliability coefficient of 0.87. Data were analyzed using descriptive statistics and the Mann–Whitney U test. Findings revealed that male leaders reported higher levels of inclusion promotion (3.65 vs. 3.25), stronger student engagement strategies (3.92 vs. 3.18), and greater concern over poor internet connectivity (3.31 vs. 2.59) than female leaders. Significant gender differences were found in inclusion practices, engagement strategies, and implementation challenges (U = 262.000; 289.500; 313.500, p = 0.001), leading to the rejection of all null hypotheses. The study concluded that gender and leadership style significantly influence the successful adoption of inclusive digital learning platforms. It further established that inadequate funding, poor connectivity, and limited assistive technologies remain major barriers. The study recommends gender-responsive leadership training, equitable allocation of digital resources, improved internet infrastructure, and sustained professional development for school leaders to strengthen inclusive digital platform adoption in secondary schools.